Pedagogical Roles and Competencies of University Teachers Practicing in the E-Learning Environment - Muñoz Carril, Pablo César; González Sanmamed, Mercedes; Hernández Sellés, Nuria (International Review of Research in Open and Distributed Learning, 2013)
Identifying the roles and competencies of faculty performing in virtual environments is crucial to higher education institutions in order to build a common frame for teaching and training initiatives. One of the goals of this study is to identify and systematize faculty’s roles through a review of the most representative surveys. There has also been an effort to identify competencies associated to every role, with an emphasis on those of the pedagogical scope, by means of a focus group. Furthermore, a cross-sectional survey with 166 faculty participants has been conducted in order to identify faculty’s level of proficiency on the pedagogical competencies and the interest in training programs. Teacher perceptions on both these aspects constitutes a relevant reference for the design of faculty training programs. Results reveal that content drafting is the aspect in which the subjects declare the highest level of proficiency as opposed to assessment. Faculty also appear to be willing to improve their training, being aware of the changes and requirements entailed by e-learning.